Characteristics of petroleum compounds and their removal from the aquatic environment - Włodarczyk-Makuła, Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the study was to characterize the components of crude oil, with particular emphasis on those that have a toxic effect on organisms, and to describe the sources of pollution and the methodology for determining these compounds in aqueous solutions. In addition, the study presents the legal provisions in the field of petroleum compounds and practical methods for their removal in the event of uncontrolled emission of these compounds into the aquatic environment as well as methods used in the treatment of wastewater loaded with these compounds.
Keywords: water; wastewater; petroleum compounds; surface water; removal petroleum compounds; PAH; BTX; woda; ścieki; związki ropopochodne; powierzchnia wody; usuwanie związków ropopochodnych